2012
DOI: 10.1007/s00132-012-1982-z
|View full text |Cite
|
Sign up to set email alerts
|

Vergleich der Behandlungsergebnisse bei kongenitalen idiopathischen und nichtidiopathischen Klumpfüßen

Abstract: This study shows good initial results after Ponseti treatment for idiopathic as well as non-idiopathic clubfeet. Based on the good functional results all clubfeet should initially be treated with the Ponseti method regardless of the etiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
1
4
0
2
Order By: Relevance
“…According to our results, recurrence was observed in 16.3% of cases with idiopathic clubfoot and 45.8% of non-idiopathic clubfoot subjects ( P = 0.001). These results are in line with the report of Gelfer et al[ 25 ] and contrary to the study by Funk et al[ 11 ] which showed no significant difference in recurrence rate between idiopathic and non-idiopathic congenital clubfeet treated using the Ponseti method. In that study, treatment of non-idiopathic cases started later and took longer than idiopathic clubfoot patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…According to our results, recurrence was observed in 16.3% of cases with idiopathic clubfoot and 45.8% of non-idiopathic clubfoot subjects ( P = 0.001). These results are in line with the report of Gelfer et al[ 25 ] and contrary to the study by Funk et al[ 11 ] which showed no significant difference in recurrence rate between idiopathic and non-idiopathic congenital clubfeet treated using the Ponseti method. In that study, treatment of non-idiopathic cases started later and took longer than idiopathic clubfoot patients.…”
Section: Discussionsupporting
confidence: 90%
“…For decades, extensive complex surgical release procedures had been the main treatment of clubfoot without acceptable long-term outcomes[ 6 , 7 ] till Ponseti published the significant result of a gentle serial manipulation and casting method to correct the deformities of clubfoot including forefoot adduction, hindfoot varus, equinus, and cavus[ 2 , 8 ]. To date, the Ponseti method is widely accepted as the gold standard for treatment of all clubfeet, regardless of the type and etiology around the world in children of 1 to 9 years of age[ 9 - 11 ]. The efficiency of the popular Ponseti method in correcting clubfoot has been well established.…”
Section: Introductionmentioning
confidence: 99%
“…6,20 Despite these difficulties, the Ponseti method is still being used as a first-line treatment for non-idiopathic CTE, and good outcomes have been reported. 6,[21][22][23][24][25]…”
Section: Non-idiopathic Ctevmentioning
confidence: 99%
“…Mehrere Studien haben bis zum heutigen Zeitpunkt gezeigt, dass es möglich ist, auch bei Grunderkrankungen wie Spina bifida, Arthrogrypose und verschiedenen mit Klumpfüßen assoziierten Syndromen eine initiale Behandlung nach dem Ponseti-Konzept erfolgreich durchzuführen [40][41][42][43]. Ebenso ist es möglich, vernachlässigte oder bereits operierte Klumpfüße nach Ponseti zu behandeln.…”
Section: Ponseti Bei Sekundären/ Nicht Idiopathischen Klumpfüßenunclassified